Mediasi Transitivitas dan Pembingkaian Ulang Ideologis dalam Terjemahan Bahasa Inggris dari Pernyataan Presiden Prabowo tentang Demonstrasi Agustus 2025 - Anandika Nugraha (Jurnal Penerjemahan, 2026)
This article examines ideological reframing via mediation in the English translation of President Prabowo Subianto’s statement on the August 2025 mass protests. Focusing on the transitivity patterns from the perspective of Halliday’s Systemic Functional Linguistics, it aims at identifying how mediation is performed through transitivity in the translation and how the mediation reframes the original ideological positioning. Using a descriptive qualitative approach, the source text and target text are segmented and analyzed to identify shifts in the process types and agent/participant visibility. The findings reveal consistent patterns of transitivity shifts, particularly in terms of intensified depictions of events via process conversion into material processes and the use of passive structures. These shifts tend to dramatize events, assert president’s authority, and blur out government’s explicit role as the subject which then reframe the original’s ideological stance. Overall, the translation demonstrates a moderate-to-high degree of mediation, highlighting the role of translation not merely as transferring message but also a means for ideology reframing. Keywords : ideology, mediation, ideational meta-function, transitivity